(untitled) (Research, Society and Development, 2019)
Due to limitations imposed by the teaching-learning environment in regular schools, it’s essential for visually impaired students to have the necessary teaching mediation in relation to the collective construction of speech objects by means of language. Using as basis Vygotsky’s Sociocultural Theory, particularly the concept of Zone of Proximal Development and Interactional Sociolinguistics, interactions between professor-visually impaired student dyads were investigated during Specialized Educational Care sessions taking place in a care institution for people with disabilities at João Pessoa, Paraiba. Two seeing teachers and two visually impaired students from the 6th and 7th year of elementary school took part in the study. 16 observation visits and 10 videography sessions were made, with two of the videos selected for microgenetics analysis. Results indicated a care similar to tutoring, prioritizing the demands coming from the regular classroom. Beyond that, joint productions of semiotic fields in teacher-student relations occurred, in which programmed and unprogrammed interactions happened, as well as the construction of speech objects through interregulation of actions. In conclusion, although ZPD emergency situations happen, one must consider the elaboration of individualized lesson plans and more frequent use of resources and materials specifically geared towards teaching-learning of visually impaired children.